Review: Peptida Bioaktif Kasein Susu Kambing sebagai Sumber Antimikroba dan Antioksidan: Review: Bioactive Peptide from Goat’s Milk Casein as a Source of Antimicrobial and Antioxidant - Venna Sinthary; Maryam Jamila Arief (Jurnal Sains dan Kesehatan, 2023)
Research on milk and its products from minor milk species has increased in the last 10 years, especially for goat milk casein. This interest was initially influenced by cow's milk intolerant consumers who chose goat's milk as an alternative nutrition. Furthermore, it underwent further review where casein in goat's milk was a potential source of bioactive peptides. The amino acid sequence associated with pharmacological activity was found in casein in cow's milk and its processed products are similar to goat's milk. The superiority of casein in goat's milk, which undergoes various post-translational modifications, leads to the production of a wide variety of casein molecules. The casein fraction is fragmented mainly enzymatically to obtain bioactive peptides that have been reported to have various activities, especially like antimicrobials and antioxidants. Keywords: Bioactive Peptides, Casein, Goat’s Milk, Antimicrobial, Antioxidant Abstrak Penelitian mengenai susu dan produknya dari spesies susu minor 10 tahun terakhir mengalami peningkatan terutama pada kasein susu kambing. Ketertarikan ini awalnya dipengaruhi oleh konsumen intoleran susu sapi sehingga memilih susu kambing sebagai alternatif. Selanjutnya mengalami peninjauan lebih lanjut dimana kasein pada susu kambing merupakan sumber peptida bioaktif potensial. Urutan asam amino berhubungan dengan aktivitas farmakologi ditemukan pada kasein susu sapi dan produk olahannya memiliki kemiripan dengan susu kambing. Keunggulan kasein susu kambing yang mengalami berbagai modifikasi pasca-translasi mengarah pada produksi berbagai macam molekul kasein. Fraksi kasein ini di fragmentasi terutama secara enzimatik untuk mendapatkan peptida bioaktif telah dilaporkan memiliki berbagai aktivitas khususnya sebagai antimikroba dan antioksidan. Kata Kunci: Peptida bioaktif, Kasein, Susu Kambing, Antimikroba, Antioksidan